Analisis Pengaruh Ketinggian Lintasan Terhadap Gaya Gesek dan Kecepatan Benda Pada Bidang Miring Menggunakan PhET Simulation - Rahmawati, Diah; Malik, Adam (Jurnal Penelitian dan Pembelajaran Fisika Indonesia, 2024)
Physics is an empirical science, meaning that physics is based on observation and experimentation. One of the fundamental concepts in physics that is the foundation for many calculations is the law of mechanical energy conservation, especially on inclined planes. This study aims to analyze the effect of track height on the friction force and velocity of objects when crossing an inclined plane. This research uses a virtual PhET Simulation laboratory with a virtual experimental research design. This research uses a quantitative approach, the data analysis technique uses statistical methods to determine the effect of track height on the friction and speed of objects. The result of this study is that the height of the track affects the value of the friction force, with increasing track height, the value of the friction force will decrease, this is due to the normal force acting on the inclined plane. In addition, with increasing track height on an inclined plane, the value of mechanical energy will increase. This is because the higher the trajectory, the greater the gravitational potential energy possessed by the object. Keywords: Altitude, Inclined plane, Mechanics, Speed.